Fatigue behavior and impedance spectrum characteristics of Cr-modified stainless-steel rebars after corrosion - Chuntao Zhang; Weishao Chen; Hongjie Zhu; Renbin An (Case Studies in Construction Materials)
Corrosion and fatigue damage of rebars are the main factors affecting the durability of reinforced concrete structures. The metallurgical industry has attempted to improve the corrosion and fatigue resistance of rebars by adding or increasing the proportion of Cr in rebars. In this study, an accelerated corrosion test of a new Cr-modified stainless-steel rebar was conducted in a laboratory, and the impedance spectrum and fatigue behavior of the corroded specimens were tested. SEM and 3D scanning were employed to analyze the corrosion products and fracture morphology. Over a 40-day corrosion period, both corrosion-product formation and corrosion rate change only marginally, and a passivation film forms on the surface, enhancing the stainless-steel rebar’s corrosion resistance. The variations in the voltage within the impedance spectrum, alterations in the capacitance radius in the Nyquist diagram, and changes in the |Z| and phase angles in the Bode diagram indicate that the main chemical mechanisms in the corrosion process are the electron loss of iron and the combination of acid and base ions. The change in the P-S-N curve and analysis of the microfracture fatigue source, crack propagation zone, and transient fracture zone shows that the stainless-steel rebar still has good resistance to fatigue damage after corrosion damage. In addition, the accuracy and feasibility of a formula derived from the integration of Weibull's probability distribution model with Paris' law were validated through computational analysis. By comparing the experimental data with the calculated values of the model, the error is less than 10 %. It can be shown that properly increasing the content of Cr in stainless-steel reinforcement has a positive promotion for improving the corrosion resistance and fatigue resistance of stainless-steel rebars. This study provides a theoretical reference for improving the corrosion resistance and fatigue behavior of stainless-steel rebars after corrosion in the metallurgical field.